Atomic structure and dynamics of epitaxial platinum bilayers on graphene - Robertson, A; Lee, G; Lee, S; Buntin, P; Drexler, M; Abdelhafiz, A; Yoon, E; Warner, J; Alamgir, F (American Chemical Society, 2019)
Platinum atomic layers grown on graphene were investigated by atomic resolution transmission electron microscopy (TEM). These TEM images reveal the epitaxial relationship between the atomically thin platinum layers and graphene, with two optimal epitaxies observed. The energetics of these epitaxies influences the grain structure of the platinum film, facilitating grain growth via in-plane rotation and assimilation of neighbor grains, rather than grain coarsening from the movement of grain boundaries. This growth process was enabled due to the availability of several possible low-energy intermediate states for the rotating grains, the Pt-Gr epitaxies, which are minima in surface energy, and coincident site lattice grain boundaries, which are minima in grain boundary energy. Density functional theory calculations reveal a complex interplay of considerations for minimizing the platinum grain energy, with free platinum edges also having an effect on the relative energetics. We thus find that the platinum atomic layer grains undergo significant reorientation to minimize interface energy (via epitaxy), grain boundary energy (via low-energy orientations), and free edge energy. These results will be important for the design of two-dimensional graphene-supported platinum catalysts and obtaining large-area uniform platinum atomic layer films and also provide fundamental experimental insight into the growth of heteroepitaxial thin films.